Influence of the semi‐rigid bolted steel joints on the frame behaviour - Daniūnas, Alfonsas; Urbonas, Kęstutis (Journal of Civil Engineering and Management, 2010)
This research work describes the analysis of steel semi rigid joints that are subjected to bending and tension or compression. The main attention is focussed on the beam‐to‐beam and plate bolted joints. Usually influence of axial force is neglected. In fact, the level of tension or compression of axial force can be significant and has some impact on joint behaviour and on its stiffness and strength characteristics. Nowadays the most powerful method for the estimation of joints characteristics is the component method. The adaptation of the component method for the determination of joints characteristics under bending ant axial forces is shown in the paper. Some numerical results of calculations of steel frameworks are presented in this paper as well (Daniūnas and Urbonas 2008). First Published Online: 24 Jun 2011